Fenomena Berjilbab di Kalangan Generasi Z: Studi Tentang Konsep Diri, Motivasi, dan Pola Interaksi Sosial di Fakultas Agama Islam UIKA Bogor - Fadhila Amalia (Jurnal Dirosah Islamiyah, 2025)
This research examines the phenomenon of wearing the hijab among Generation Z, with a focus on self-concept, motivation and social interaction patterns at the Faculty of Islamic Religion, Ibn Khaldun University (UIKA) Bogor. This phenomenon originates from the Islamic religious view which emphasizes the importance of Muslim women covering their private parts as a form of identity and compliance with sharia. However, developments in the digital era and fashion trends influence the way the younger generation, including students, view the concept of wearing the hijab. The aim of this research is to understand the self-concept, motivation, and social interaction patterns that shape female students' decisions to wear the hijab on campus. The research method used is a phenomenological approach, which aims to explore participants' perspectives in depth. Data was collected through interviews, observation and documentation of ten female students at the Islamic Faculty of UIKA Bogor from various semester levels. The research results show that female students' self-concept regarding the hijab is closely related to their identity as Muslim women who adhere to religious teachings. The main motivation for wearing the hijab is obedience to Allah's commands, accompanied by the influence of family, friends and inspirational figures on social media. The hijab also has a positive impact on social interaction patterns, where female students feel more respected and supported by their community. The conclusion of this research shows that the hijab has an important role in shaping identity and social interaction patterns among Generation Z, especially in the campus environment. For Islamic Faculty students, the hijab is not only a religious symbol, but also a reflection of personal dedication to Islamic values and a source of personal pride.